Diffused peace facilitation and the cosmopolitan filmmaker’s dilemma - Kalnes, Øyvind and Bakøy, Eva (Media, War & Conflict, 2017)
This article discusses the dilemmas documentary filmmakers face when acting upon the cosmopolitan ethos in a context of ongoing civil warfare and peace facilitation from the international society. This ethos is well known and accepted among Western audiences. When applied outside the Western hemisphere, the perspective of human-interest stories tends to get lost among audiences attached to the conflict. Instead, these stories may easily become identified as new public diplomacy on behalf of the participants on the ‘perceptual battlefield’ of war. The authors focus upon how this can be a challenge for Western states involved in peace processes in the same conflicts, especially for those small states that have little hard power and have to rely on gaining the trust of the conflicting parties. The article uses a case study of the Norwegian documentary My Daughter the Terrorist about the civil war in Sri Lanka as an example. The film became the epicentre of a major controversy during a critical stage in the peace process facilitated by the Norwegian government. The authors suggest the concept of diffused war can be translated as diffused peace facilitation to describe its effect on the peace process.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNzUwNjM1MjE2NjYxNjQ3